1992
DOI: 10.1002/mop.4650050614
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and scattering by thin wires with a dielectric coating—a finite‐difference time‐domain approach

Abstract: This Letter discusses the computation of the scattering and radiation by thin wires with a nondispersive dielectric coating using the finite‐difference time‐domain method. A Fourier transform is then performed on the time‐domain results to obtain the scattering and antenna radiation patterns in the frequency domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…It was found that the results from [11] were indistinguishable from those obtained using the method of [12] so only the latter are included in the figures.…”
Section: Results For a Wire Dipolementioning
confidence: 86%
See 3 more Smart Citations
“…It was found that the results from [11] were indistinguishable from those obtained using the method of [12] so only the latter are included in the figures.…”
Section: Results For a Wire Dipolementioning
confidence: 86%
“…Calculations were performed using standard FDTD, method 1 as described in [7], method 2 as described in [12], and method 3 as presented in this contribution. It was found that the results from [11] were indistinguishable from those obtained using the method of [12] so only the latter are included in the figures.…”
Section: Results For a Wire Dipolementioning
confidence: 99%
See 2 more Smart Citations
“…In [2] the field assumption of the tangential magnetic and the radial electric field near a thin wire were incorporated in the update equations. Later, these subcell models were improved for wires with dielectric coatings [3], for wire end effects [4] and for bundles of wires [5]. A lot of researchers have also investigated the development of subcell models for thin slots.…”
Section: Introductionmentioning
confidence: 99%